Energy efficient comparator for successive approximation register ADCs with application to encryption schemes in wireless communication. Issue 14 (28th August 2013) - Yuan, Shitong; Liang, Jing; Liang, Qilian; Ren, Jian; Liang, Jing; Zhang, Baoju; Pi, Yiming; Zhao, Chenglin
Abstract Security is a very broad topic; particular attention has been paid in communications, networking on security issues. However, in practical applications, providing security services increases the computation and the occupation of system resources. This problem is particularly important when the energy is a limited resource for mobile communication devices operating on battery. Thus, energy efficient security devices are very necessary for the communication. This paper designed a new low voltage, low power consumption comparator for successive approximation register analog to digital converter to improve the energy efficiency in the problem of secure communication. Then, analyze the energy consumption of the new comparator security system compared with traditional design. We mainly focus on three communication protocols, which use the block cipher. The results show that the system's energy consumption is greatly reduced when the new comparator is used, Copyright © 2013 John Wiley & Sons, Ltd.